2019
DOI: 10.31227/osf.io/g9ecb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Karakteristik bahasa arab

Abstract: Bahasa Arab adalah salah satu alat komunikasi yang dengannya manusia dapat berinteraksi satu sama lain. Selain itu, bahasa arab memiliki keistimewaan tersendiri daripada bahasa bahasa yang lain yaitu bahasa utama umat islam, sebagai bahasa Al Quran dan Hadist, dan bahasa surga yang In Sha Allah kita nanti berada didalamnya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The results of Uyun (2022), research shows that blended learning learning can improve student learning outcomes. A similar study conducted by Musdalifa et al, (2020) showed that there was a positive influence on the use of blended learning based on the Edmodo social network in the discovery learning model on the cognitive learning outcomes of students on the buffer solution material.…”
Section: Introductionmentioning
confidence: 76%
“…The results of Uyun (2022), research shows that blended learning learning can improve student learning outcomes. A similar study conducted by Musdalifa et al, (2020) showed that there was a positive influence on the use of blended learning based on the Edmodo social network in the discovery learning model on the cognitive learning outcomes of students on the buffer solution material.…”
Section: Introductionmentioning
confidence: 76%
“…Several studies presented the improvement of the physicochemical properties of extracts from C. ternatea after microencapsulation. Microencapsulation can maintain the intensity of anthocyanin color from C. ternatea extract [13,78,80,81]. The extract of C. ternatea microencapsulated with maltodextrin, cassava flour-maltodextrin, and gelatin-maltodextrin showed high solubility in water, around 99%, which was caused by the water-soluble encapsulants used, primarily maltodextrin [13].…”
Section: Physicochemical Properties Of Microencapsulated C Ternateamentioning
confidence: 99%
“…Hal ini mampu menimbulkan konsepsi yang berbeda dari setiap siswa. Salah satu konsepsi yang berbeda tersebut disebut dengan miskonsepsi [4].…”
Section: Pendahuluanunclassified